Lips2lips: Terminal year end report - Chua, Peter A. (Animo Repository, 2022)
Lips2lips is a startup business that aims to break the stereotype that skincare products are only for women and focused on providing solutions to chapped, dry, and aging lips that both men and women experience. It produces lip balms that are 100% organic which not only moisturizes but also prevents lips from cracking.